Malware forensics field guide for Windows systems digital forensics field guides - Malin, Cameron H. (Syngress, 2012)
Dissecting the dark side of the Internet with its infectious worms, botnets, rootkits, and Trojan horse programs (known as malware) is a treaterous condition for any forensic investigator or analyst. This title presents a tool with checklists for specific tasks, case studies of difficult situations, and analyst tips.